2021
DOI: 10.1093/ofid/ofab525
|View full text |Cite
|
Sign up to set email alerts
|

Crushing and Splitting Direct-Acting Antivirals for Hepatitis C Virus Treatment: A Case Series and Literature Review

Abstract: Limited data exist regarding the use of direct-acting antivirals (DAAs) for hepatitis C virus (HCV) in patients who are unable to swallow tablets. This case series describes HCV treatment in patients requiring tablet manipulation, providing evidence for safety and effectiveness of HCV DAA tablet manipulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Additionally, successful treatment of chronic HCV infection with crushed GLE/PIB via percutaneous gastrostomy tube has been reported in three adults. 5 Our two cases document real-world success with early nasoenteric administration of crushed and dissolved GLE/PIB for ddHCV in two young adult cardiac transplant recipients, one of whom completed his entire 12-week course via NGT and achieved SVR12. These cases provide evidence for nasoenteric GLE/PIB administration that enables earlier DAA initiation following transplantation with organs from HCV-viremic donors.…”
Section: E T T E R T O T H E E D I T O Rmentioning
confidence: 83%
“…Additionally, successful treatment of chronic HCV infection with crushed GLE/PIB via percutaneous gastrostomy tube has been reported in three adults. 5 Our two cases document real-world success with early nasoenteric administration of crushed and dissolved GLE/PIB for ddHCV in two young adult cardiac transplant recipients, one of whom completed his entire 12-week course via NGT and achieved SVR12. These cases provide evidence for nasoenteric GLE/PIB administration that enables earlier DAA initiation following transplantation with organs from HCV-viremic donors.…”
Section: E T T E R T O T H E E D I T O Rmentioning
confidence: 83%
“…These outcomes led some institutions to delay initiation of GLE/PIB until patients could reliably tolerate oral medications and swallow the tablets whole. A recently published case series showed 100% SVR in ten patients treated with various DAA regimens, including GLE/PIB tablets that were split or crushed for oral or percutaneous endoscopic gastrostomy (PEG) tube administration 43 . Similarly, their review of the available literature identified an additional 11 cases which reported 100% SVR with tablet manipulation of various DAA regimens.…”
Section: Discussionmentioning
confidence: 99%
“…The availability of the age‐appropriate formulations is still a major global concern. Recent evidence suggests that tablet manipulation (halving and crushing) does not impact the safety and effectiveness of HCV DAA 46 …”
Section: Monitoring Of Treatment With Daa In Children With Chronic He...mentioning
confidence: 99%
“…Recent evidence suggests that tablet manipulation (halving and crushing) does not impact the safety and effectiveness of HCV DAA. 46…”
Section: Monitoring Of Treatment With Daa In Children With Chronic He...mentioning
confidence: 99%